A four-stage fifth-order trigonometrically fitted semi-implicit hybrid method for solving second-order delay differential equations - Ahmad, Sufia Zulfa; Ismail, Fudziah; Senu, Norazak (Hindawi Publishing Corporation, 2016)
We derived a two-step, four-stage, and fifth-order semi-implicit hybrid method which can be used for solving special second-order ordinary differential equations. The method is then trigonometrically fitted so that it is suitable for solving problems which are oscillatory in nature. The methods are then used for solving oscillatory delay differential equations. Numerical results clearly show the efficiency of the new method when compared to the existing explicit and implicit methods in the scientific literature.